Meninos traídos: abuso sexual e constituição da masculinidade - Andre Assis Breder de Oliveira (2017)
The vicissitudes of the father-son relationship and of traumatism in the form of sexual abuse are contemplated in this dissertation that aims to open a debate regarding the sexual violation of boys perpetrated by men who are identification references for them. Seeking to present a psychoanalytical approach of the betrayals impact on the masculine identity in these affective relationships that ought to be ethical and stable, we followed the defensive motion in testimonies and clinical cases of the literature in which it is possible to observe the unauthorization of the significance of the traumatic event itself and its unfolding, such as dissociative states and identification with the aggressor as a viable alternative to preserve elements of the masculine identification. The setting of this study is framed by the lack of room provided by the culture for the victim-man and by the fundamentally defensive quality of masculinity. Following the proposals of S. Bleichmar, we verified the embarrassment caused by the chaotic aspect of trauma in relation to the constitution of masculinity since the process is characterized by the fundamental paradox in which the boy has to incorporate the fathers penis in order be covered with potency and legitimize his sexual place. Thus, the thorny quality of the relation between sexual abuse and male identity supplants theproblematic around sexual orientation as it imposes a transitivity that revives the homosexualghosts that threaten the identitys nucleus and haunt the betrayed boys with the possibilitythat, outside of the rigid virile frame of masculinity, they, in fact, cannot be men.